LANCL1 binds abscisic acid and stimulates glucose transport and mitochondrial respiration in muscle cells via the AMPK/PGC-1α/Sirt1 pathway - Spinelli, Sonia (Mol Metab, 2021)
OBJECTIVE: Abscisic acid (ABA) is a plant hormone also present and active in animals. In mammals, ABA regulates blood glucose levels by stimulating insulin-independent glucose uptake and metabolism in adipocytes and myocytes through its receptor LANCL2. The objective of this study was to investigate whether another member of the LANCL protein family, LANCL1, also behaves as an ABA receptor and, if so, which functional effects are mediated by LANCL1. METHODS: ABA binding to human recombinant LANCL1 was explored by equilibrium-binding experiments with [(3)H]ABA, circular dichroism, and surface plasmon resonance. Rat L6 myoblasts overexpressing either LANCL1 or LANCL2, or silenced for the expression of both proteins, were used to investigate the basal and ABA-stimulated transport of a fluorescent glucose analog (NBDG) and the signaling pathway downstream of the LANCL proteins using Western blot and qPCR analysis. Finally, glucose tolerance and sensitivity to ABA were compared in LANCL2(−/−) and wild-type (WT) siblings. RESULTS: Human recombinant LANCL1 binds ABA with a K(d) between 1 and 10 μM, depending on the assay (i.e., in a concentration range that lies between the low and high-affinity ABA binding sites of LANCL2). In L6 myoblasts, LANCL1 and LANCL2 similarly, i) stimulate both basal and ABA-triggered NBDG uptake (4-fold), ii) activate the transcription and protein expression of the glucose transporters GLUT4 and GLUT1 (4-6-fold) and the signaling proteins AMPK/PGC-1α/Sirt1 (2-fold), iii) stimulate mitochondrial respiration (5-fold) and the expression of the skeletal muscle (SM) uncoupling proteins sarcolipin (3-fold) and UCP3 (12-fold). LANCL2(−/−) mice have a reduced glucose tolerance compared to WT. They spontaneously overexpress LANCL1 in the SM and respond to chronic ABA treatment (1 μg/kg body weight/day) with an improved glycemia response to glucose load and an increased SM transcription of GLUT4 and GLUT1 (20-fold) of the AMPK/PGC-1α/Sirt1 pathway and sarcolipin, UCP3, and NAMPT (4- to 6-fold). CONCLUSIONS: LANCL1 behaves as an ABA receptor with a somewhat lower affinity for ABA than LANCL2 but with overlapping effector functions: stimulating glucose uptake and the expression of muscle glucose transporters and mitochondrial uncoupling and respiration via the AMPK/PGC-1α/Sirt1 pathway. Receptor redundancy may have been advantageous in animal evolution, given the role of the ABA/LANCL system in the insulin-independent stimulation of cell glucose uptake and energy metabolism.